Effectiveness of optimized food-based recommendation promotion to improve nutritional status and lipid profiles among Minangkabau women with dyslipidemia: A cluster-randomized trial - Gusnedi Gusnedi; Umi Fahmida; Fiastuti Witjaksono; Fariz Nurwidya; Muchtaruddin Mansyur; Ratna Djuwita; Cesilia Meti Dwiriani; Murdani Abdullah (BMC, 2022)
Abstract Background In women of Minangkabau ethnicity, a high prevalence of dyslipidemia, overweight, and obesity is thought to be closely related to poor dietary practices. Promotion of local specific food-based recommendations (FBRs) was previously found to be effective in improving dietary practice and nutrient intakes related to dyslipidemia. This study aimed to describe the effects of the FBR promotion on the nutritional status and lipid profiles of Minangkabau women with dyslipidemia. Methods We used a cluster-randomized design with a total subject of 123 Minangkabau women of reproductive age with dyslipidemia. They were recruited from 16 sub-villages and assigned to either the FBR group (n = 61) or the non-FBR group (n = 62). Data on body weight, height, waist circumference, and lipid profiles were collected at the baseline and the end of the trial. Linear mixed model analysis was used to analyze the effect of the intervention on nutritional status and lipid profiles. Results The mean effect (95% confidence interval) of the intervention on body weight, body mass index, and waist circumference for the FBR group versus the non-FBR group were -1.1 (-1.8; -0.39) kg, -0.43(-0.76; -0.11) kg/m2 and -2.1(-3.7;-0.46) mm respectively (p <0.05). The Castelli's index in the FBR group improved, but there was no significant between-group difference in the change of total cholesterol, LDL cholesterol, HDL cholesterol, and triglycerides at the end of the intervention. Conclusion The promotion of the FBRs positively impact the nutritional status but did not significantly affect the blood lipid profile of Minangkabau women with dyslipidemia. Trial Registration The trial was retrospectively registered at ClinicalTrials.gov Protocol Registration and Result System (PRS) as NCT04085874, in September 2019.